Utilizing the Analytical Hierarchy Process (AHP) for Spatial Development Prioritization in Hama Region (Journal of Hama University, 2026)
This study employs the Analytical Hierarchy Process (AHP), a multi-criteria decision-making methodology, to identify the most suitable District for initiating spatial development in Hama Region, prioritizing district with the most urgent developmental needs. The research methodology involved a two-phase expert consultation process. In the first phase, a panel of 10 experts participated in a structured questionnaire designed to determine the most influential criteria in the selection process. In the second phase, the same experts applied AHP to assign weights to these criteria and evaluate the target districts accordingly. The analysis, conducted using Super Decisions software, revealed that economic conditions were the most critical factor, receiving the highest weight (33%), followed by infrastructure availability (26%). The criteria of economic development potential and population density ranked next, with respective weights of 21% and 13%, while environmental conditions had the least influence, with a weight of 6%. Based on the assigned weights, Harbanafsah emerged as the most pressing priority for spatial development, making it the optimal starting point for intervention in Hama Region. Furthermore, a sensitivity analysis was conducted to examine the impact of changes in criteria weights on the final ranking. The results indicated that modifying the weights of infrastructure availability and environmental conditions would make the Hama Governorate Center the most suitable area for development. These findings underscore the importance of criteria weighting in spatial decision-making and highlight the necessity of a flexible and adaptive approach in regional planning efforts.
Keywords: Spatial development – Analytic Hierarchy process (AHP) - Hama district